Comets and Moons: The For-another in Hegel’s Philosophy of Nature - Reid, Jeffrey (Université d'Ottawa | University of Ottawa, 2014)
This paper examines the Hegelian moment of the for-another in its negative relation to the other moment of particularity: the for-itself. I identify the dissolving, fluidifying action of the for-another by examining figures within the Philosophy of Nature, particularly comets and moons but also Hegel’s physics of light and sound. The dissolution of the lunar for-itself at the hands of the cometary for-another illustrates how the dynamic relation between the two moments of particularity participates in the presentation of essence, within the Hegelian syllogism, i.e. as mediating between the universal and the singular. The dynamic action of cometary negativity occurs throughout the Philosophy of Nature and therefore should be pivotal to how the work is read.
Keywords: Hegel; syllogism; Philosophy of Nature; logic; particularity